Caroperla brevihamata (Plecoptera: Perlidae), a new stonefly species from Guangxi Zhuang Autonomous Region of southern China - Mo, Raorao; Liu, Hong; Liao, Debao; Wang, Guoquan; Li, Weihai (Zootaxa, 2020)
A new species of the genus Caroperla Kohno, 1946, C. brevihamata Mo, Wang & Li, sp. nov., is described from the Huaping National Nature Reserve of northeastern Guangxi Zhuang Autonomous Region of southern, China. The relationships based on morphological characteristics of the new species and related species are discussed.